ANTROPHOMETRI DAN AKSESBILITAS DIFABEL PADA TOILET UMUM PORTABEL DI SURAKARTA - Hapasari, Putri Sekar (Institut Seni Indoensia Surakarta, 2017)
Public toilets for persons with disabilities were important tool used as a support for the smooth functioning of disabled persons in the public sphere. Portable public toilets were usually used to supportcertain activities that were considered incapable of being facilitated by permanent toilets. This studyaims to determine the level of anthrophometry and accessibility of people with disabilities in portabletoilets in Surakarta. To find out if the disabled people had difficulty or even felt the ease and comfortwhen using the facility. Anthrophometric measurements were essential to see if they fitted their dimensions with the needs of the users, especially those with disabilities.The research object was a portable public toilet located on Jl. Slamet Riyadi Surakarta. The methodused is descriptive with qualitative approach supported by quantitative data, or could also be calleddouble research strategy that was the use of various methods in solving a research problem. Quantitative here using numerical data from field observation measurements, then compared with referencesand in the analysis based on interpretation of researchers taken from field data and interviewees.The results of the research were expected to be input to the Surakarta City Government and otherstakeholders, in order to provide a good public facility in accordance with the rules of anthrophometryof portable public toilets that could be made to function optimally. The results of this study were alsoexpected to provide teaching material on Interior Design Study Program ISI SurakartaKeywords: Disable accessibility Anthrometry,